Viral Infections in HSCT: Detection, Monitoring, Clinical Management, and Immunologic Implications - Annaloro, Claudio; Serpenti, Fabio; Saporiti, Giorgia; Galassi, Giulia; Cavallaro, Francesca; Grifoni, Federica; Goldaniga, Maria; Baldini, Luca; Onida, Francesco (Frontiers in Immunology, 2021)
In spite of an increasing array of investigations, the relationships between viral infections and allogeneic hematopoietic stem cell transplantation (HSCT) are still controversial, and almost exclusively regard DNA viruses. Viral infections per se account for a considerable risk of morbidity and mortality among HSCT recipients, and available antiviral agents have proven to be of limited effectiveness. Therefore, an optimal management of viral infection represents a key point in HSCT strategies. On the other hand, viruses bear the potential of shaping immunologic recovery after HSCT, possibly interfering with control of the underlying disease and graft-versus-host disease (GvHD), and eventually with HSCT outcome. Moreover, preliminary data are available about the possible role of some virome components as markers of immunologic recovery after HSCT. Lastly, HSCT may exert an immunotherapeutic effect against some viral infections, notably HIV and HTLV-1, and has been considered as an eradicating approach in these indications.